2014
DOI: 10.1080/03643107.2013.853008
|View full text |Cite
|
Sign up to set email alerts
|

Principled Leadership Development Model for Aspiring Social Work Managers and Administrators: Development and Application

Abstract: There is an emerging trend in social work administration where many direct practice-oriented social work students get promoted after their graduation to supervisory or managerial positions, yet haven't mastered macro-level competencies during their social work education. This places these recent graduates in the untenable position of stepping into professional roles they didn't envision and might not be prepared for. This may inhibit their advancement in administrative hierarchies because they do not have the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Many of the problems, with which LIS is contending today and which are raised in our article, are not unique. Other professionally oriented fields – social work, for example – also find themselves in the middle of debate on such issues as accreditation, the theory–practice gap, balancing theoretical education and skill-based training, the social and scientific status of the profession, the effects of professionalization on the core professional mission, the growing importance of leadership skills for entry-level professionals and the need for relying on evidence-based practices while developing a dialogue and building relationships with communities they serve (Bliss et al , 2014; Brekke, 2012; Martinez-Brawley et al , 2011; Miller and Skinner, 2013; Watson et al , 2001; Werkmeister and Grady, 2011). LIS researchers interested in education, the academia–field connection and the image of the profession may benefit from collaboration and dialogue with scholars and practitioners in other fields and from learning about their experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the problems, with which LIS is contending today and which are raised in our article, are not unique. Other professionally oriented fields – social work, for example – also find themselves in the middle of debate on such issues as accreditation, the theory–practice gap, balancing theoretical education and skill-based training, the social and scientific status of the profession, the effects of professionalization on the core professional mission, the growing importance of leadership skills for entry-level professionals and the need for relying on evidence-based practices while developing a dialogue and building relationships with communities they serve (Bliss et al , 2014; Brekke, 2012; Martinez-Brawley et al , 2011; Miller and Skinner, 2013; Watson et al , 2001; Werkmeister and Grady, 2011). LIS researchers interested in education, the academia–field connection and the image of the profession may benefit from collaboration and dialogue with scholars and practitioners in other fields and from learning about their experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that virtual asynchronous classroom experiences were effective for teaching MSW students and that students who are prepared in generalist practice and social work administration are overlooked for nonprofit leadership (Williams-Gray, 2014). Furthermore, Bliss et al (2014) support the Principled Leadership Development Model for addressing the gap in social work leadership. This model can create adaptable leadership development initiatives for social workers in their professional careers.…”
Section: Preparing Social Work Leadersmentioning
confidence: 92%
“…This model can create adaptable leadership development initiatives for social workers in their professional careers. This model introduced six integrated components: a) underpinning ethical principles, b) core leadership competencies, c) domain-specific leadership competencies, d) integrative practice opportunities and mentoring support, e) ongoing self-reflection and continued growth, and f) evaluation (Bliss et al, 2014). These components can be applied to leadership development among individuals pursuing a Master's of Social Work degree and/or continuing education and professional development.…”
Section: Preparing Social Work Leadersmentioning
confidence: 99%
“…Social workers have been found to use a systemic perspective to solve complex human service problems and a relational leadership style (Adams, 2018;Rank & Hutchison, 2000). In addition, arguments in support of SW leaders have stated that SW leaders bring to HSOs the necessary ethical, principled leadership style (Bliss, Pecukonis, & Snyder-Vogel, 2014), knowledge of direct practice that remains the bedrock of the profession (Brilliant, 1986), and commitment to social justice (Sullivan, 2016). Ethical leadership has been shown to translate to ethical practice (Mayer et al, 2009;Schaubroeck et al, 2012).…”
Section: Social Work Leadershipmentioning
confidence: 99%